ANALYSIS OF COMMON SIZE ON BSI (BANK SYARIAH INDONESIA) IN 2020-2021 - Harley Agustian; Rico Nur Ilham; Irada Sinta; Bob Feinberg (PT. Radja Intercontinental Publishing, 2023)
This research is motivated by the condition of the financial performance of Bank Indonesia Syariah. In the 2020 balance sheet financial statements, there is an increase, as well as in 2021, again experiencing an increase of 265 billion rupiah. This study measures financial performance with common size analysis. This research is a type of quantitative research. The research in this paper is focused on common size analysis at Bank Indonesia Syariah in 2020-2021. The theoretical approach that the researcher uses is: descriptive-analysis, the financial statements of Bank Indonesia Syariah can be analyzed using common size analysis. The results of this study are common size analysis at Bank Indonesia Syariah in 2020-2021. On the balance sheet: assets have increased. While on the income statement, revenue has increased, and the expense account has decreased. In the balance sheet, there was an increase in assets from 239.581 billion in 2020 to 265.289 billion in 2021. The increase in assets occurred in accounts receivable, marketable securities and cash, as well as other assets. Likewise in the income statement, there is an increase in profit from 2.187 billion in 2020 to 3.028 billion in 2021.